2020
DOI: 10.22271/j.ento.2020.v8.i5af.7825
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of ixodid tick fauna in domestic animals of Andhra Pradesh state, India

Abstract: Tick infestation in domestic animals is one of the serious health problems throughout the globe, especially in tropical countries. The present study was conducted to determine the prevalence and diversity of ixodid tick fauna of domestic animals from all 13 districts of Andhra Pradesh state, India. The study was conducted from May 2019 to March 2020. A total of 870 cattle, 602 buffaloes, 736 sheep, 754 goats, and 492 dogs were examined and out of which 717 (82.41%), 441 (73.26%), 592 (80.43%), 604 (80.11%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Results recorded on total prevalence and prevalence in canines, cattle and cat are represented in Table 2 to 5. Anish et al (2000) identified 8 species of ticks in cattle, buffaloes, sheep, goats, and dogs from Andhra Pradesh, India. Shobana et al (2013) reported 14 species of ticks from 5 genera in domestic animals (cats, dogs, goats and buffalo) of Villupuram District, South India.…”
Section: Resultsmentioning
confidence: 99%
“…Results recorded on total prevalence and prevalence in canines, cattle and cat are represented in Table 2 to 5. Anish et al (2000) identified 8 species of ticks in cattle, buffaloes, sheep, goats, and dogs from Andhra Pradesh, India. Shobana et al (2013) reported 14 species of ticks from 5 genera in domestic animals (cats, dogs, goats and buffalo) of Villupuram District, South India.…”
Section: Resultsmentioning
confidence: 99%